Calif. EV drivers to lose carpool lane perk - Boigon, Molly (Automotive News, 2025)
[...]qualifying vehicles must be 100 percent electric or hydrogen-fuel cell vehicles, plug-in hybrids that meet certain conditions or compressed natural gas vehicles that meet certain conditions. Wallis, the California lawmaker, authored a bill that extended the state program until Jan. 1, 2027, pending extended federal authorization. The Republican-led Congress has introduced a bill to eliminate the individual $7,500 EV tax credit.